1989
DOI: 10.1152/ajpheart.1989.257.5.h1750
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for adenosine receptor-mediated hyperpolarization in coronary smooth muscle

Abstract: The effects of adenosine and its analogues, 5'-N-ethyl-carboxamidoadenosine (NECA) and 2-chloroadenosine (CAD), were studied on resting membrane potential of bovine coronary artery. The resting membrane potential averaged -51 +/- 1 mV. KCl (50 mM) caused a significant decrease of the resting membrane potential (-30 +/- 1 mV). In separate series of experiments suffusion of the arterial strips with adenosine, NECA, or CAD, at concentrations of 10(-5)M, produced significant increases in resting membrane potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Adenosine receptor-mediated hyperpolarisation of bovine and porcine coronary artery smooth muscle was reported [428,429]. Adenosine was found also to hyperpolarise cultured guinea pig coronary endothelial cells; this finding supports the hypothesis that the hyperpolarisation of the endothelium induced by adenosine released into the perivascular space of the capillaries may be conducted electrotonically to the terminal arterioles and may cause vasodilation via current flow through myoendothelial gap junctions [430].…”
Section: Coronary Blood Vesselssupporting
confidence: 54%
“…Adenosine receptor-mediated hyperpolarisation of bovine and porcine coronary artery smooth muscle was reported [428,429]. Adenosine was found also to hyperpolarise cultured guinea pig coronary endothelial cells; this finding supports the hypothesis that the hyperpolarisation of the endothelium induced by adenosine released into the perivascular space of the capillaries may be conducted electrotonically to the terminal arterioles and may cause vasodilation via current flow through myoendothelial gap junctions [430].…”
Section: Coronary Blood Vesselssupporting
confidence: 54%
“…The membrane potential of vascular smooth muscle cells is very sensitive to the open-state probability of KATP channels ). Glibenclamide has been reported to be a specific blocker of KATP channels (see Ashcroft & Ashcroft, 1990) which binds directly to the channel protein (Bernardi, Fosset & Lazdunski, 1988;Boyd, AguilarBryan & Nelson, 1990 (Sabouni, Hargittai, Lieberman & Mustafa, 1989). In a recent study on rabbit coronary arteries (diameter, 300 ,um) it was found that both adenosine (0-3-3 Experiments with adenosine antagonists like 8-PT and adenosine uptake inhibitors like dipyridamole have often been used as tests for the adenosine hypothesis (reviewed by Berne, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that the cell isolation method itself may reduce the size of the responses to adenosine. In a microelectrode study on bovine coronary artery 10 /ZM adenosine was found to produce a hyperpolarization of about 17 mV (Sabouni, Hargittai, Lieberman & Mustafa, 1989). Hyperpolarization will lead to decreased Ca2" entry through voltage-dependent Ca2" channels.…”
Section: The Mechanisms Of Adenosine-induced Vasodilatationmentioning
confidence: 93%